Wandering through the Mesolithic. An archaeostatistical approach to explore the mobility patterns in eastern Iberia. (August 2019) - Cortell-Nicolau, Alfredo; García-Puchol, Oreto; Barton, C. Michael; Diez-Castillo, Agustín; Pardo-Gordó, Salvador
Abstract: Tracing hunter-gatherer's mobility has been a recurring topic both in anthropological and archaeological literature. Following Binford's approach (1980), ethnographic comparisons have been brought out in order to better understand mobility patterns among Palaeolithic and Mesolithic groups, and how they relate with their environment, thus formulating a system where a main difference in mobility structure is pronounced on the distinction between residential and logistical camps. After some efforts made in order to relate the lithic record with such model (Clark and Barton, 2017), in this work we explore how lithic industry can be a reliable proxy for understanding the mobility patterns of the last hunter-gatherers of the Eastern Iberian Peninsula by studying a number of Late Mesolithic lithic collections. We try to bring a new insight into Clark and Barton's analysis, both by combining different sites -implementing geographical variability- and by taking into account functionality and its possible statistical traces, as shown by blades, bladelets and geometric microliths. We focus on the differences found at each site and how they relate with lithic industry in order to test hypotheses regarding mobility patterns. Highlights: Different statistical tools for measuring hunter-gatherers' mobility by their lithic industry are tested. Diverse functionality of the sites can serve as an approach to mobility. Sites from the Late Mesolithic in the Eastern part of the Iberian Peninsula are used as case studies. Binford's mobility proposal is tested for these particular societies.